PROPOSING DIYAT AS AN ALTERNATIVE TO DEATH PENALTY FOR THE CRIME OF MURDER IN MALAYSIA - Ismail, Siti Zubaidah (Jurnal Syariah, 2024)
Pressure has increased on retentionist countries, including Malaysia, to consider finding an alternative penalty to the death penalty for murder. In mid-2023, the government decided to abolish the mandatory death penalty and proposed alternative sentences for the crime of murder. Concurrently, the concept of diyat or Islamic monetary compensation has also been raised by many quarters for consideration. This article examines the concept of forgiveness and diyat and addresses the potential impact of incorporating them into Malaysian criminal law. Employing a normative empirical method, the study utilized literature from predominantly secondary sources. Normative analysis was conducted to describe the findings. It is found that diyat has the potential to replace the death penalty for intentional killing, provided that amendments to the law are made. Most importantly, the victim’s heirs must grant forgiveness. This is because the victim’s family holds the right to decide whether to accept diyat, demand retribution or pardon the offender entirely. The core changes required include amendments to the Penal Code and Criminal Procedure Code. This article contributes to the existing literature on the harmonization of Islamic principles and law, and explores the potential applicability of Islamic law within the Malaysian legal system.